2008
DOI: 10.1902/jop.2008.080192
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation Markers in Patients With Aggressive Periodontitis: A Pilot Study

Abstract: Patients with AgP may have elevated peripheral leukocyte numbers and serum globulin levels as well as decreased serum albumin levels and albumin/globulin ratios compared to controls. These changes might be associated with the severity of periodontal destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
44
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 31 publications
11
44
1
Order By: Relevance
“…The secretion of cytokines also promotes production of lymphocytes [55,56]. The white blood cell count was found to be higher in CP patients in our study which is consistent with Shi’s study [57]. …”
Section: Discussionsupporting
confidence: 90%
“…The secretion of cytokines also promotes production of lymphocytes [55,56]. The white blood cell count was found to be higher in CP patients in our study which is consistent with Shi’s study [57]. …”
Section: Discussionsupporting
confidence: 90%
“…WBC is useful clinically as an index of conditions involving inflammation . It was demonstrated that a positive association existed between periodontitis and WBC . In the present study, the association between BMI and WBC count was a U‐shaped relationship as well, and 22 was the optimal BMI associated with the lowest WBC count.…”
Section: Discussionsupporting
confidence: 65%
“…WBC (white blood count) is useful clinically as an index of a variety of conditions, particularly those involving inflammation . Numerous researches demonstrated that WBC was positively correlated with periodontitis . Kweider et al.…”
mentioning
confidence: 99%
“…It is used to examine the changes in overall protein secretion in biologic fluids or to look for differences in the ratio of specific proteins to total protein that occur in response to physiological changes. Measurement of total protein was used to normalize concentrations of various salivary proteins in different samples since concentrations can vary significantly in response to stimulation or alterations of saliva flow [17][18][19][20].…”
Section: Measurement Of Total Protein and Balpmentioning
confidence: 99%